The Benefit of Application-Based Education Using the Healthy Lungs Version 2.0 on Inhaler Adherence Among Patients with Chronic Obstructive Pulmonary Disease at RS Prof. Dr. Chairuddin P. Lubis - Muhammad Pany Al-A’raf; Amira Permata Sari Tarigan; Andika Pradana (Journal of Society Medicine, 2026)
Introduction: Chronic obstructive pulmonary disease (COPD) is a leading cause of morbidity and mortality worldwide. Inhalation therapy is central to management; however, suboptimal adherence and incorrect inhaler technique contribute to poor disease control and recurrent exacerbations. Application-based education provides continuous, standardized, accessible instruction that may improve adherence to inhaler therapy. The Healthy Lungs application 2.0 was developed in the Philippines for COPD patients to evaluate its educational effectiveness on inhaler adherence at RS Prof. Dr. Chairuddin P. Lubis, University of North Sumatra, Indonesia. Methods: An analytical study with a case–control approach enrolled 50 patients with COPD selected by consecutive sampling. Inhaler adherence was assessed with a structured questionnaire before and after the application-based intervention. Normality was examined with the Kolmogorov–Smirnov test, and pre- versus post-intervention adherence was compared using the Wilcoxon signed-rank test, with significance set at p < 0.05. Results: The respondents were predominantly elderly (43%) and male (58%). Before the intervention, low adherence predominated (50%); afterwards, the proportion with high adherence rose to 42%, with most respondents improving and few declining. The Wilcoxon test demonstrated a significant difference in adherence before and after the intervention (Z = –3.196; p = 0.001), with a large effect size (Cohen's d = 1.05). Conclusion: Education delivered through the Healthy Lungs app significantly improved inhaler adherence among patients with COPD, supporting its use as an adjunct to conventional inhaler counseling.